Comparison of Two Techniques for the Treatment of Recurrent Pterygium: Amniotic Membrane vs Conjunctival Autograft Combined with Mitomycin C. (2nd November 2015) - Katırcıoglu, Yasemin Arslan; Altiparmak, Ugur; Engur Goktas, Seniz; Cakir, Burcin; Singar, Evin; Ornek, Firdevs
Abstract: Purpose : To compare the results of amniotic membrane transplantation (AMT) combined with mitomycin C (MMC) to the results of free conjunctival autograft (CA) combined with MMC for the treatment of patients with recurrent pterygium. Methods : In this prospective study, 60 eyes of 55 patients with recurrent pterygium were included and randomly assigned into group I ( n  = 30) who underwent AMT combined with MMC (AMT-MMC) and group II ( n  = 30) who underwent CA combined with MMC (CA-MMC). During a mean follow-up of 27.2 ± 20.8 months, recurrence of pterygium, change in uncorrected visual acuity and complications (including pain, corneal, conjunctival or scleral changes) were analyzed and were compared between groups. Results : Five eyes of 5 patients were lost to follow-up and were removed from analysis. The mean age ( p  = 0.274), the mean follow-up ( p  = 0.063), the number of prior pterygium excision surgeries ( p  = 0.641) and the mean preoperative visual acuity ( p  = 0.959) were similar in both groups. Recurrence was seen in 2 eyes (8%) in AMT-MMC group and 4 patients (13.3%) in CA-MMC group ( p  = 0.531). Postoperative visual acuity ( p  = 0.237), change in visual acuity ( p  = 0.525), severe pain ( p  = 0.531) and epithelial defect lasting more than 5 days ( p  = 0.510) were similar in both groups. Conclusions : Amniotic membrane combined with MMC has similar recurrence rate to CA combined with MMC, in patients with recurrent pterygium. Similar outcomes and complication rates make AMT-MMC a promising method for the treatment of recurrent pterygium cases.